2004
DOI: 10.1186/1743-8454-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic capabilities of the choroid plexus epithelium in Alzheimer's disease

Abstract: As the secretory source of vitamins, peptides and hormones for neurons, the choroid plexus (CP) epithelium critically provides substances for brain homeostasis. This distributive process of cerebrospinal fluid (CSF) volume transmission reaches many cellular targets in the CNS. In ageing and ageing-related dementias, the CP-CSF system is less able to regulate brain interstitial fluid. CP primarily generates CSF bulk flow, and so its malfunctioning exacerbates Alzheimers disease (AD). Considerable attention has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 107 publications
1
38
0
Order By: Relevance
“…The primary pathologic change in iNPH is disturbed CSF circulation (Johanson et al., 2004), for which CSF shunt operations are primarily performed (Kazui, Miyajima, Mori, & Ishikawa, 2015). While a study demonstrated the effectiveness of LP shunting in 2015 (Kazui et al., 2015), the selection is presently made according to the patient's condition and surgeon's experience (Anderson, Grant, de la Paz, Frucht, & Goodman, 2002; Klinge, 2012; Klinge, Hellstrom, Tans, & Wikkelso, 2012; Klinge, Marmarou, Bergsneider, Relkin, & Black, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The primary pathologic change in iNPH is disturbed CSF circulation (Johanson et al., 2004), for which CSF shunt operations are primarily performed (Kazui, Miyajima, Mori, & Ishikawa, 2015). While a study demonstrated the effectiveness of LP shunting in 2015 (Kazui et al., 2015), the selection is presently made according to the patient's condition and surgeon's experience (Anderson, Grant, de la Paz, Frucht, & Goodman, 2002; Klinge, 2012; Klinge, Hellstrom, Tans, & Wikkelso, 2012; Klinge, Marmarou, Bergsneider, Relkin, & Black, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The choroid plexus is a highly vascularized tissue that is present in all brain ventricles, and whose primary function is the production and renewal of the main constituents of the CSF (Johanson et al, 2004; Liddelow et al, 2012). The inner stroma of the choroid plexus is richly irrigated by fenestrated capillaries (Wolburg and Paulus, 2010), allowing the free passage of circulating molecules and immune cells, into this compartment.…”
Section: Choroid Plexus In Admentioning
confidence: 99%
“…Under healthy conditions, however, the blood-CSF barrier (BCSFB) formed by the choroid plexus epithelial cells restricts immune-cell entry into the CSF and the brain parenchyma (Baruch and Schwartz, 2013; Engelhardt et al, 2001; Hasegawa-Ishii et al, 2013). AD patients exhibit major alterations in choroid plexus structure and morphology, as well as in epithelial cell function, attributable mainly to the increase in toxic Aβ peptides (Brkic et al, 2015; Johanson et al, 2004; Vargas et al, 2010). In addition, the ability of epithelial cells to express the transporters that participate in Aβ efflux, as well as to secrete Aβ-scavenging proteins into the CSF and their corresponding receptors, decreases with age and is compromised in different in-vitro and in-vivo models of AD (Antequera et al, 2009; Crossgrove et al, 2005; Zlokovic et al, 1996).…”
Section: Choroid Plexus In Admentioning
confidence: 99%
“…CP consists of a dense collection of capillaries in an ependymal stroma surrounded by a layer of epithelium [12]. The CP of the lateral ventricles contain several materials that could possibly bind to FTP, including melanin [13], calcification/mineralization [14], Biondi rings [15, 16], and iron deposits [17]. Monoamine oxidase A has also been cited as a source of off-target binding [10, 18].…”
Section: Introductionmentioning
confidence: 99%